The influence of local emissions and regional air pollution transport on a European air pollution hot spot - Kozáková, Jana; Pokorná, Petra; Vodička, Petr; Ondráčková, Lucie; Ondráček, Jakub; Křůmal, Kamil; Mikuška, Pavel; Hovorka, Jan; Moravec, Pavel; Schwarz, Jaroslav (Environmental science and pollution research international, 2019)
The EU air quality standards have been frequently exceeded in one of the European air pollution hot spots: Ostrava. The aim of this study was to perform an air quality comparison between an urban site (Radvanice), which has a nearby metallurgical complex, and a suburban site (Plesná) to estimate air pollution sources and determine their local and/or regional origins. Twenty-four hour PM1 and PM10 (particular matter) concentrations, detailed mass size distributions (MSDs) to distinguish the sources of the fine and coarse PM, and their chemical compositions were investigated in parallel at both sites during the winter of 2014. Positive matrix factorization (PMF) was applied to the PM1 and PM10 chemical compositions to investigate their sources. During the measurement campaign, prevailing northeastern-southwestern (NE-SW) wind directions (WDs) were recorded. Higher average PM10 concentration was measured in Radvanice than in Plesná, whereas PM1 concentrations were similar at both sites. A source apportionment analysis revealed six and five sources for PM10 and PM1, respectively. In Radvanice, the amount of PM and the most chemical species were similar under SW and NE WD conditions. The dominant sources were industrial (43% for PM10 and 27% for PM1), which were caused by a large metallurgical complex located to the SW, and biomass burning (25% for PM10 and 36% for PM1). In Plesná, the concentrations of PM and all species significantly increased under NE WD conditions. Secondary inorganic aerosols were dominant, with the highest contributions deriving from the NE WD. Therefore, regional pollution transport from the industrial sector in Silesian Province (Poland) was evident. Biomass burning contributed 22% and 24% to PM10 and PM1, respectively. The air quality in Ostrava was influenced by local sources and regional pollution transport. The issue of poor air quality in this region is complex. Therefore, international cooperation from both states (the Czech Republic and Poland) is needed to achieve a reduction in air pollution levels.
Keywords: velkoměsta; Česká republika; Wind; znečištění ovzduší; velikost částic; Air Pollution; Cities; vítr; Poland; Czech Republic; Particulate Matter; Polsko; Environmental Monitoring; monitorování životního prostředí; Particle Size; pevné částice